Connectivity of the human insula: A cortico-cortical evoked potential (CCEP) study. (November 2019) - Dionisio, Sasha; Mayoglou, Lazarus; Cho, Sung-Min; Prime, David; Flanigan, Patrick M.; Lega, Bradley; Mosher, John; Leahy, Richard; Gonzalez-Martinez, Jorge; Nair, Dileep
Abstract: Objective: The human insula is increasingly being implicated as a multimodal functional network hub involved in a large variety of complex functions. Due to its inconspicuous location and highly vascular anatomy, it has historically been difficult to study. Cortico-cortical evoked potentials (CCEPs), utilize low frequency stimulation to map cerebral networks. They were used to study connections of the human insula. Methods: CCEP data was acquired from each sub-region of the dominant and non-dominant insula in 30 patients who underwent stereo-EEG. Connectivity strength to the various cortical regions was obtained via a measure of root mean square (RMS), calculated from each gyrus of the insula and ranked into weighted means. Results: The results of all cumulative CCEP responses for each individual gyrus were represented by circro plots. Forty-nine individual CCEP pairs were stimulated across all the gyri from the right and left insula. In brief, the left insula contributed more greatly to language areas. Sensory function, pain, saliency processing and vestibular function were more heavily implicated from the right insula. Connections to the primary auditory cortex arose from both insula regions. Both posterior insula regions showed significant contralateral connectivity. Ipsilateral mesial temporal connections were seen from both insula regions. In visual function, we further report the novel finding of a direct connection between the right posterior insula and left visual cortex. Significance: The insula is a major multi-modal network hub with the cerebral cortex having major roles in language, sensation, auditory, visual, limbic and vestibular functions as well as saliency processing. In temporal lobe epilepsy surgery failure, the insula may be implicated as an extra temporal cause, due to the strong mesial temporal connectivity findings.